2023
DOI: 10.3389/ti.2023.10959
|View full text |Cite
|
Sign up to set email alerts
|

Twenty Years of Unspecified Kidney Donation: Unspecified Donors Looking Back on Their Donation Experiences

Abstract: The Netherlands was the first European country to implement unspecified kidney donation in 2000. This qualitative study aimed to evaluate the experiences of unspecified kidney donors (UKDs) in our transplant institute to improve the care for this valuable group of donors. We conducted semi-structured interviews with 106 UKDs who donated between 2000–2016 (response rate 84%). Interviews were audio-recorded, transcribed verbatim and independently coded by 2 researchers in NVivo using thematic analysis. The follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…This is in line with the current study, which found that some staff acknowledged that some UKDrs struggled with the requirement for anonymity, principally due to a strong psychological need for connection with the recipient. This correlates with a paper by Pronk et al which identified that some UKDrs remained troubled by and curious about the lack of contact with their recipient many years after their donation [ 42 ]. Future studies need to probe this issue both from the perspective of the recipient as well as the donor to determine if there is a mutual reciprocal benefit that challenges the current rules around anonymity.…”
Section: Discussionsupporting
confidence: 81%
“…This is in line with the current study, which found that some staff acknowledged that some UKDrs struggled with the requirement for anonymity, principally due to a strong psychological need for connection with the recipient. This correlates with a paper by Pronk et al which identified that some UKDrs remained troubled by and curious about the lack of contact with their recipient many years after their donation [ 42 ]. Future studies need to probe this issue both from the perspective of the recipient as well as the donor to determine if there is a mutual reciprocal benefit that challenges the current rules around anonymity.…”
Section: Discussionsupporting
confidence: 81%
“…The selected studies originated from various countries, including the United States [ 42 , 43 , 44 , 45 , 46 , 47 ], the UK [ 3 , 48 ], Denmark [ 49 , 50 ], the Netherlands [ 51 ], Japan [ 52 ], Canada [ 53 ], Australia [ 4 ], and across Canada and Australia [ 54 , 55 ]. Thus, most of the research comes from Western countries.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, another donor reported the following: "I shared a story about my kidney donation of Facebook, to spread the word about living kidney donation". [51] For certain donors, donations appear to have facilitated the deepening of existing relationships:…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Living donation is at a crossroads in medicine with a greater need for organs for patients waiting for transplants. Current studies therefore deal with the psychological repercussions of such a procedure on the donor and on the psychological evaluation of him or her in the living donor process [4]. At present, recommendations do not require living donors to have a psychological evaluation before donation but it is nevertheless "strongly recommended" [5].…”
Section: Introductionmentioning
confidence: 99%